2015
DOI: 10.1080/09540253.2015.1008421
|View full text |Cite
|
Sign up to set email alerts
|

Between a rock and a hard place: women and computer technology

Abstract: This paper explores certain possible reasons behind the uneasy relationship between women and technology. The cultural identification of technology with masculinity has been well documented through previous research. However, we feel it is useful to revisit this complex relationship through the scope of a more subtle distinction between 'users' and 'connoisseurs', and the struggle over power, which revolves around a specific form of hegemonic masculinity. We draw on interviews that examine students' experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…Other factors include the stereotypical view that girls have about studies and jobs related to ICT and their unfamiliarity about what really means to work in this field (Castaño and Webster 2011;Clayton, von Hellens and Nielsen 2009;Klapwijk and Rommes 2009;Master, Cheryan and Meltzoff 2016;Pechtelidis, Kosma and Chronaki 2015;Schott and Selwyn 2000;Thomas and Allen 2006;von Hellens, Clayton, Beekhuyzen and Nielsen 2009). Thomas and Allen (2006) carried out an exploratory research on boys' and girls' perceptions about ICT careers.…”
Section: Professional Stereotypesmentioning
confidence: 99%
“…Other factors include the stereotypical view that girls have about studies and jobs related to ICT and their unfamiliarity about what really means to work in this field (Castaño and Webster 2011;Clayton, von Hellens and Nielsen 2009;Klapwijk and Rommes 2009;Master, Cheryan and Meltzoff 2016;Pechtelidis, Kosma and Chronaki 2015;Schott and Selwyn 2000;Thomas and Allen 2006;von Hellens, Clayton, Beekhuyzen and Nielsen 2009). Thomas and Allen (2006) carried out an exploratory research on boys' and girls' perceptions about ICT careers.…”
Section: Professional Stereotypesmentioning
confidence: 99%
“…If women become professionally interested in computers, they are more likely to choose jobs where computers are used to play a care role, in line with traditional expectations of women (for example, ICT in education). Pechtelidis, Kosma, and Chronaki (2015) described this process as a clever adaptation by women to the expectations of a male-dominated field, while at the same time maintaining traditional family roles. Many publications have shown that girls and women are less keen to work with a computer or to apply ICT programs or ICT instruments compared with boys and men (Volman & van Eck, 2001;Losh, 2004;Becker, 2006;Madigan et al, 2007;Kubiatko, 2010;Zhao et al, 2010;van Deursen & van Dijk, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The international research literature on computing education continues to confirm a concerning under-representation of women in the IT sector [14], [30] and worrying results about gender impact [23]. In the recent past, computer use and activities related to ICT were seen as a field of "male domination" [7] and this perception continues today, despite slight improvements in gender balance [26]. Even though recent research [23] confirms the persistence of the gender gap, there is strong evidence to support the thesis that teaching educational robotics to students can have a positive effect on their subject choices [6].…”
Section: Robotics In Primary Educationmentioning
confidence: 99%